2020
DOI: 10.1186/s12891-020-03453-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of arthroscopic internal drainage of popliteal cysts with or without cyst wall resection

Abstract: Background This study aimed to compare the arthroscopic internal drainage of popliteal cysts alone or in combination with cyst wall resection in terms of clinical outcomes. Methods Forty-two consecutive patients with symptomatic popliteal cysts received arthroscopic treatment. Specifically, 20 of them received arthroscopic internal drainage (AI group) alone and 22 received arthroscopic internal drainage combined with cyst wall resection (AICR group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Zhou et al 21 suggested in a Meta analysis of published works on surgical treatment of popliteal cysts between 1980 and July 2015 that arthroscopy was an ideal option to treat intra-articular lesions, expand the communication port and resect the cyst wall. Su C et al 22 reported in a recent study that popliteal cysts disappeared completely and shrunk in 81.8% and 18.2% of all patients when combining AID with CWR, and the cyst survival rate was 0%, which indicated a further decline in the recurrence rate compared with arthroscopic decompression of simple intra-articular lesions without giving rise to such intra-operative complications as nerve and vascular injury mentioned in other published studies. This finding was proven by this study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Zhou et al 21 suggested in a Meta analysis of published works on surgical treatment of popliteal cysts between 1980 and July 2015 that arthroscopy was an ideal option to treat intra-articular lesions, expand the communication port and resect the cyst wall. Su C et al 22 reported in a recent study that popliteal cysts disappeared completely and shrunk in 81.8% and 18.2% of all patients when combining AID with CWR, and the cyst survival rate was 0%, which indicated a further decline in the recurrence rate compared with arthroscopic decompression of simple intra-articular lesions without giving rise to such intra-operative complications as nerve and vascular injury mentioned in other published studies. This finding was proven by this study.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, AID has been extensively recognized as a treatment strategy for patients with popliteal cysts. [15][16][17][18][19] However, AID combined with treatment of intra-articular lesions without CWR remains controversial as this may lead to the recurrence of the cyst. Zhang et al 20 discovered that the popliteal cyst wall was histologically comprised of thickened tissues of glassy degeneration, without any synovial cells.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“… 3 , 5 In contrast, arthroscopic treatment of intra-articular lesions, arthroscopic popliteal cyst resection or internal drainage, or open popliteal cyst resection have achieved satisfactory clinical results. 4 , 5 , 6 , 8 Nonetheless, the latter approach is rarely used because it requires altering the surgical position of the patient, and secondary disinfection needs to be performed during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with arthroscopic popliteal drainage, the arthroscopic popliteal cyst resection has a lower postoperative recurrence rate, but it significantly increases the operation time and postoperative complications. 4 , 6 We propose the knee medial double approach for removal of popliteal cysts, which can be completed about 5 minutes, thus significantly reducing the operation time. At the same time, as the intraoperative perfusion time is greatly shortened, the incidence of postoperative complications is also lower and the recovery faster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation